Enterprise Architecture Model for the Mortgage Loan Lending Process in a Financial Institution Using TOGAF - Flores-Chavez, Oscar Alonso (2024)
Mortgage loans in financial institutions have evolved thanks to digital transformation, employing emerging technologies to streamline their processes, enhance customer service, and improve the customer experience. This research presents an enterprise architecture considering the development of its three domains: business, applications, and technology, for the financial institution under study. Additionally, we present technological solutions to manage customer verification, pre-qualification, credit assessment, and property evaluation. The proposal and its technological solutions include the enhancement of the mortgage loan lending process in terms of management, reduction of manual tasks, in-person activities at branches, and document submission for credit and property evaluation. In this regard, we use TOGAF and its ADM development methodology. Finally, the model was evaluated based on 5 dimensions with a panel of experts using the Delphi technique, resulting in a 94% acceptance level and a total of 17 items that achieved a high level of consensus. This indicates that the implementation of the model will help optimize the mortgage loan process.